Challenges of Business Education in Asia - Viswanathan, G (Institutional Knowledge at Singapore Management University, 2011)
Education creates “Human Capital” and Social Capital”. Higher Education Institutions, Colleges and Universities have played a significant role in the economic and social development of the nations and will continue to do so. However, their role will become increasingly significant in view of internationalization and globalization of higher education. Present and future scenario in respect of higher education in Asia, the strategies to be adopted for establishing Higher Education institutions and for their expansion, key performance indicators of Higher Education and how Higher Education institutions become key drivers for economic and societal development are presented in this paper. The challenges facing Higher Education such as huge investments, equity and inclusiveness consistent with quality providing relevant education and training are also highlighted in this paper.